Antihyperglycaemic activity of the flavonoid-rich fraction of the extract of Tamarindus indica L. on experimentally induced hyperglycaemic wistar rats - Yerima M, Anuka J.A, Salawu O.A, Abdu-Aguye I. and Tanko Y (Journal of Applied Pharmaceutical Science, 2014)
Diabetes is the most common endocrine disease and its prevalence is reaching epidemic proportion worldwide. Tamarindus indica is a slow growing tree that is resistant to strong winds and perennial. The stem-bark extract of the plant is used locally for the management of diabetes. The objective of this work was to investigate the potentials of the flavonoid-rich portion of Tamarindus indica at lowering elevated blood glucose level. The flavonoids-rich portion of the stem-bark extract of Tamarindus indica L. was investigated for its hypoglycemic action on experimentally induced hyperglycaemic Wistar rats. The oral LD50 of the extract was found to be 1,265 mg/kg. The flavonoid-rich fraction lowered the Blood Glucose Level (BGL) in the three doses used (100, 200 and 400 mg/kg) there was a significant reduction with the 400 mg/kg dose at the 8th, 16th and 24th hour and the 200 mg/kg dose at 16 and 24 hours, and the 100 mg/kg dose at 24 hours. The flavonoid-rich portion of Tamarindus indica Linn significantly lowered elevated BGL in the experimental animal models.
Keywords: Alloxan,fructose,Hyperglycemia,metformin,Tamarindus indica.